The Effectiveness of a Training Program Based on Positive Emotions Theory in Developing the Psychological Capital: An Experimental Study on Secondary School Teachers in Ouargla City- - Bencheikh, Rabiaa; Benzahi , Mansour (Dirasat: Educational Sciences, 2024)
Objectives: The study aimed to uncover the level of psychological capital among secondary school teachers in the state of Ouargla and to assess the effectiveness of a training program based on Fredrickson's theory of positive emotions in developing their psychological capital. Methods: To achieve the study's objectives, two data-collection tools were used. The first tool was the Psychological Capital Questionnaire developed by Luthans and colleagues (2007) after being adapted to the context. The second tool was a training program based on the theory of positive emotions for developing psychological capital, created by the researchers. By adopting a quasi-experimental design, the study was conducted on a sample of (40) male and female teachers of English and French in secondary education in Ouargla. The participants were divided into an experimental group and a control group using a non-randomized two-group pretest-posttest design. Results: The results indicated that the level of psychological capital among secondary school teachers in Ouargla was low. Statistically significant differences in psychological capital were found between the two groups (control and experimental) in the post-test measurement, favoring the experimental group. This suggests that the training program based on Fredrickson's theory of positive emotions was effective in developing the psychological capital of secondary school teachers. Conclusions: The study recommends the importance of focusing on personal development resources and utilizing the theoretical framework of positive emotions theory to achieve this goal.